2016
DOI: 10.18203/2319-2003.ijbcp20163153
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of the aqueous-methanolic Moringa oleifera (Lam) leaf extract on female Wistar albino rats

Abstract: Background: Herbal preparations are widely assumed to be safe on oral administration and therefore the documentation of the toxic potential of some herbal concoctions used as medicine and nutrients is limited. Moringa oleifera (MO) is a plant that is gaining tremendous popularity in rural communities in Kenya as a means of offsetting nutritional and medicinal needs. However, very little is known about the safety of the plant on oral administration. Thus, the aim of the current study was to assess the biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
1
15
1
Order By: Relevance
“…The LD50 of the aqueous methanol extract of M. oleifera leaves was found to be greater than 2000 mg/kg in female wistar albino rats [41], while in the current study the LD50 of the methanolic extract was 3458.3 mg/kg in male wistar albino mice. Kasolo et al, (2011) reported that, the LD50 values of the ethanolic and aqueous extracts of M. oleifera roots growing in Uganda were 17.8 g/kg and 15.9 g/kg, respectively [42].…”
Section: General Sign and Behavioral Analysiscontrasting
confidence: 66%
“…The LD50 of the aqueous methanol extract of M. oleifera leaves was found to be greater than 2000 mg/kg in female wistar albino rats [41], while in the current study the LD50 of the methanolic extract was 3458.3 mg/kg in male wistar albino mice. Kasolo et al, (2011) reported that, the LD50 values of the ethanolic and aqueous extracts of M. oleifera roots growing in Uganda were 17.8 g/kg and 15.9 g/kg, respectively [42].…”
Section: General Sign and Behavioral Analysiscontrasting
confidence: 66%
“…From our previous studies on acute oral toxicity of MO [14], a 1000 mg/kg dose of the aqueous-methanol MO leaf extract was used in evaluating hepatoprotective activity against AS-AQ intoxication. Thirty six rats were randomly assigned to 12 groups (each 3 animals) based on the Acute Toxic Class method [15].…”
Section: Experimental Designmentioning
confidence: 99%
“…21,27,28 There is a general misguided perception that herbal preparations are safe and thus the documentation of the toxic potential of herbal medicine and nutrients remains elusive. 29 A majority of the reports touching on the toxicity of herbal medicines are often associated with hepatotoxicity 30 yet toxic effects may also manifest at cellular level in the various body systems. 31 In the current study, we sought to determine the cytotoxic effects of crude extracts of D. integrifolia on Vero cell lines using the MTT assay.…”
Section: Discussionmentioning
confidence: 99%